Technologies for Development of Feelings of Loyalty to the Fatherland in Students of Military Education (Journal of Pedagogical Inventions and Practices, 2023)
in this article, on the basis of "Technology for the development of a sense of loyalty to the Motherland among cadets of military education before conscription", the younger generation is brought up in loyalty to the Motherland, the Motherland. religious, courageous and courageous, highly qualified and highly moral people Opinions are given about the special role of educational centers.